The implementation of authentic assessment through project-based learning to improve student's problem solving ability and concept mastery of environmental pollution topic - Andanawarih, M; Diana, S; Amprasto, A (Journal of physics. Conference series, 2019)
This study aims to obtain the information about improving of student's problem solving ability and concept mastery after the implementation of authentic assessment through project-based learning of environmental pollution topic. The subject of the study were 10th grade students consist of 40 students in a senior high school in Bandung. The research method was weak experiment with the one-group pretest-posttest design. The instruments used for this research are the test of problem solving ability and concept mastery, completed with observation sheet, questionnaire as student's responses, product assessment and student's worksheet. Student's problem solving ability was measured by pre-test and post-test questions referred to the problem solving aspect of Marzano while concept mastery was measured by pre-test and post-test referred to Revised Bloom's Taxonomy. Data were analyzed using quantitative way with N-Gain value. Student's problem solving ability showed the point of N-Gain 0,72 while the concept mastery N-Gain 0,70. The results of the study shows that the implementation of authentic assessment through project-based learning can improve student's problem solving ability and concept mastery with high category.